On the problem of the existence and uniqueness of right triangles - Kirjackis, Jevgenijus; Mazėtis, Edmundas; Melničenko, Grigorijus (Lietuvos matematikos rinkinys, 2017)
In the article necessary and sufficient conditions for existence and uniqueness of a right triangle with given bisector and median are established.
Keywords: right triangle; median; bisector; cubic equation